How do family members of individuals with spinal cord and acquired brain injuries make sense of their experiences: A qualitative study of meaning making processes. Issue 1 (March 2020) - Geard, Anne; Kirkevold, Marit; Løvstad, Marianne; Schanke, Anne-Kristine
This study explores the processes that promote coping with abruptive life changes, often experienced as life before and after injury. The consept of meaning making, was used as theoretical framework for analysisthr. Family members of individuals with spinal cord and acquired brain injury participated in two focus groups three to twenty years post-injury. Data was analysed using thematic analyses. Two main themes were identified: drawing upon different coping strategies and balancing family needs against personal autonomy. Making sense of an altered situation was by keeping a positive outlook, making comparisons to worst cases, engagement in activities and making room for own needs. Thus, the study illistrates that life can continue in a good manner after adversities, but requires flexibility and adjustments.